2019
DOI: 10.25077/jif.10.1.53-62.2018
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Anomali Sinyal Geomagnetik Ultra Low Frequency Sebagai Prekursor Gempa Bumi Dengan Magnitudo Kecil Di Wilayah Kepulauan Nias

Abstract: Telah dilakukan identifikasi anomali sinyal geomagnetik frekuensi rendah sebagai prekursor gempa bumi dengan magnitudo kecil di wilayah Kepulauan Nias. Pada penelitian ini digunakan data gempa dari bulan September 2016 hingga bulan Juni 2017 dengan rentang waktu data geomagnetik yang digunakan 30 hari sebelum terjadinya gempa bumi. Data geomagnetik ini adalah data yang terekam oleh sensor Magnetic Acquisition Data System (MAGDAS). Penyeleksian data gempa bumi dilakukan dengan menerapkan persamaan radius daerah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies have identified ULF signal anomalies as precursors to earthquakes with small magnitudes in the Nias Islands region, using geomagnetic data 30 days before the earthquake. It was found that there were 3 earthquakes with ULF signal anomalies, and the ULF anomaly lead time for the three earthquakes had a shorter duration than previous studies in the Sumatra region with large earthquakes 8 Observations analyzing signal anomalies were carried out using the Detrended Fluctuation Analysis method for a large earthquake of magnitude 6.1 in the Lebak region of Banten. This is a follow-up study to previous observations that found ULF signal anomalies 7 and 11 days before the earthquake occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified ULF signal anomalies as precursors to earthquakes with small magnitudes in the Nias Islands region, using geomagnetic data 30 days before the earthquake. It was found that there were 3 earthquakes with ULF signal anomalies, and the ULF anomaly lead time for the three earthquakes had a shorter duration than previous studies in the Sumatra region with large earthquakes 8 Observations analyzing signal anomalies were carried out using the Detrended Fluctuation Analysis method for a large earthquake of magnitude 6.1 in the Lebak region of Banten. This is a follow-up study to previous observations that found ULF signal anomalies 7 and 11 days before the earthquake occurred.…”
Section: Introductionmentioning
confidence: 99%